PENGARUH PROMOSI KESEHATAN DENGAN MEDIA POSTER TERHADAP PENGETAHUAN IBU TENTANG KANKER PAYUDARA - I Nyoman Ehrich Lister (Jurnal Maternitas Kebidanan, 2020)
According to the World Health Organization (WHO) in 2013 in Depkes RI (2015), the incidence of cancer in the year 2008 to 2012 has increased from 12.7 million cases increased to 14.2 million cases. The purpose of this study is to determine the Influence of Health Promotion By method of posters against the knowledge of mothers about breast cancer. The method in this research is queasy experimental with pre-test and post-test group design. This study was conducted in Environment II the Village of Tanjung Gusta Medan which was held in June 2019. The population of the study was 322 people, the sampling technique using random sampling with the solving formula. Methods collection data in this research use the primary data i.e. the pre-test and post-test. Data analysis was used in univariate and bivariate with the Chi-Square test. The results of this study indicate the pre-test some mothers are knowledgeable both as much as 4 people (17.4%), and post-test as many as 15 people (65.2%), knowledgeable enough at the time of the pre-test as many as 18 people (78.3%), and post-test as many as 6 people (26.1%), and less knowledgeable at the time of the pre-test as many as 1 person (4.3%), post-test as much as 2 people(8.7%). Based on this research concluded that a good knowledgeable in knowing the definition of breast cancer, the factors that cause breast cancer, how to prevent breast cancer, and how to perform a breast cancer screening